Managing Opioid Withdrawal Symptoms During the Fentanyl Crisis: A Review - Weber AN; Trebach J; Brenner MA; Thomas MM; Bormann NL (Dove Medical Press, 2024)
Andrea Nicole Weber,1 Joshua Trebach,2 Marielle A Brenner,2 Mary Margaret Thomas,3 Nicholas L Bormann4 1Department of Psychiatry, University of Iowa, Iowa City, IA, USA; 2Department of Emergency Medicine, University of Iowa, Iowa City, IA, USA; 3Hardin Library for the Health Sciences, University of Iowa, Iowa City, IA, USA; 4Department of Psychiatry and Psychology, Mayo Clinic, Rochester, MN, USACorrespondence: Andrea Nicole Weber, Department of Psychiatry, University of Iowa, 500 Newton Road, 1-308 MEB, Iowa City, IA, 52242, USA, Tel +1-319-335-6980, Fax +1-319-384-7467, Email andrea-n-weber@uiowa.eduAbstract: Illicitly manufactured fentanyl (IMF) is a significant contributor to the increasing rates of overdose-related deaths. Its high potency and lipophilicity can complicate opioid withdrawal syndromes (OWS) and the subsequent management of opioid use disorder (OUD). This scoping review aimed to collate the current OWS management of study populations seeking treatment for OWS and/or OUD directly from an unregulated opioid supply, such as IMF. Therefore, the focus was on therapeutic interventions published between January 2010 and November 2023, overlapping with the period of increasing IMF exposure. A health science librarian conducted a systematic search on November 13, 2023. A total of 426 studies were screened, and 173 studies were reviewed at the full-text level. Forty-nine studies met the inclusion criteria. Buprenorphine and naltrexone were included in most studies with the goal of transitioning to a long-acting injectable version. Various augmenting agents were tested (buspirone, memantine, suvorexant, gabapentin, and pregabalin); however, the liberal use of adjunctive medication and shortened timelines to initiation had the most consistently positive results. Outside of FDA-approved medications for OUD, lofexidine, gabapentin, and suvorexant have limited evidence for augmenting opioid agonist initiation. Trials often have low retention rates, particularly when opioid agonist washout is required. Neurostimulation strategies were promising; however, they were developed and studied early. Precipitated withdrawal is a concern; however, the rates were low and adequately mitigated or managed with low- or high-dose buprenorphine induction. Maintenance treatment continues to be superior to detoxification without continued management. Shorter induction protocols allow patients to initiate evidence-based treatment more quickly, reducing the use of illicit or non-prescribed substances.Keywords: synthetic opioids, treatment, diagnosis, prevention, addiction medicine